MicroRNA-196b promotes gastric cancer progression by targeting ECRG4. Issue 2 (February 2021) - Chen, Liao; Tang, Huirong; Liu, Guobin; Xiao, Shufeng; Liang, Daoming; Ma, Jun; Yang, Yanlong; Luo, Haibo; Zhu, Yong; Xie, Fujia; Cheng, Xi; Chi, Junlin; et al.
Abstract : Gastric cancer is one of the most common malignant tumors. MicroRNA-196b (miR-196b) has been demonstrated to play important roles in human cancers. However, its functions in gastric cancer progression were still largely unknown. In this study, the expression of miR-196b was determined by quantitative real-time PCR. Esophageal cancer-related gene 4 ( ECRG4 ) level was examined by western blot assay and immunohistochemistry staining assay. Cell proliferation was evaluated by Cell Counting Kit-8 (CCK-8) assay and colony formation assay. Cell migration and invasion were analyzed by transwell assay. The association between miR-196b and ECRG4 was analyzed by dual-luciferase reporter assay. The functional role of miR-196b in vivo was analyzed by murine xenograft assay. As a result, we found the expression of miR-196b was elevated and the protein expression of ECRG4 was reduced in gastric cancer tissues and cells. MiR-196b inhibition suppressed gastric cancer cell proliferation, migration and invasion. ECRG4 was a target of miR-196b and its protein expression was negatively regulated by miR-196b. Moreover, ECRG4 overexpression showed similar effects with miR-196b inhibition on the malignant behaviors of GC cells and ECRG4 knockdown reversed the effects of miR-196b inhibition on gastric cancer cell proliferation, migration and invasion. In addition, miR-196b inhibition suppressed tumor volume and weight in vivo . In conclusion, downregulation of miR-196b inhibited gastric cancer progression by modulating ECRG4 expression, indicating that miR-196b might be a potential therapeutic target for gastric cancer.